On a duality between Time and Space Cones - Waleed Al-Qallaf; Kyriakos Papadopoulos (Kuwait Journal of Science)
We give an exact mathematical construction of a spacelike order $<$, which is dual to the standard chronological order $\ll$ in the $n$-dimensional Minkowski space $M^n$, a construction that can be extended to any curved spacetime, and we discuss its geometrical as well as its topological implications.